City! Washington, D.C - Climo, Shirley; Ancona, George (New York : Macmillan ; Toronto : Collier Macmillan : New York : Maxwell Macmillan International, 1991)
Describes the building, history, and significant sights of Washington, D.C.
Includes index.
Highschool to College student
Keywords: Washington (D.C.) -- Guidebooks -- Juvenile literature; Washington (D.C.) -- Juvenile literature; Washington (D.C.)